Percutaneous Atrial Septal Defect (ASD) closure technique in case of association with an azygos continuation of the inferior vena cava “case report” - Zaoui, Nassime; Boukabous, Amina; Bachir, Nadhir; Terki, Ali; Irid, Nabil (Journal of Cardiology and Cardiovascular Medicine, 2022)
Introduction: Atrial Septal Defect (ASD) is the most common congenital heart disease, accessible to percutaneous closure in 90% of cases. The closure procedure is performed usually under local anesthesia and TTE by femoral access. The association of OS-ASD with an azygos continuation of the inferior vena cava is very rare (< 0.1/1000 births) making femoral access impossible. Only a few cases are mentioned in the literature, here we describe the procedure as faithfully as possible. Important clinical finding: We present a case of a 32-years-old female candidate for percutaneous closure of OS-ASD with right cavity dilatation who present during her procedure an unusual guidewire path suspecting an azygos continuation of the inferior vena cava, confirmed by CT angiography, making impossible the closure via the femoral approach. Therapeutic intervention: After being confronted with the categorical patient refusal of the surgery, we performed successfully the procedure; one month later; under general sedation by internal jugular approach. We finished with manual compression before extubating the patient. Outcomes: The follow-up was favorable at the cost of a hematoma at the puncture site and brachial plexus compression, which regressed after 3 days. Conclusion: We opted for general anesthesia and intubation to guide the procedure by TEE. We placed it in the aorta, which gave us good stability to continue successfully the procedure. We underestimated the risk of complication at the puncture site, which could have been avoided by using a vascular suture device or more prolonged compression. Main takeaway lesson: Percutaneous closure is the reference treatment for OS-ASD. In case of is associated with an azygos continuation of the inferior vena cava, the right internal jugular vein remains a reasonable approach; it requires discussion and rigorous preparation by the whole team. The management of the puncture site in this situation remains delicate and requires great concentration.